Adaptation and Exploratory Factor Analysis of the Parent Problem Checklist: Indonesian Version for New Parents - Tahlia Latifah; Sri Redatin Retno Pudjiati (G-Couns: Jurnal Bimbingan dan Konseling, 2026)
The transition to parenthood increases vulnerability to interparental conflict, especially in cultural contexts where parenting roles are strongly emphasized. However, valid tools to assess such conflict in Indonesia remain scarce. This study aimed to adapt the Parent Problem Checklist (PPC) into Indonesian and examine its psychometric properties. A total of 711 new parents participated. The adaptation process followed Beaton’s guidelines, including translation, expert review, and readability testing. Factor validity was assessed using Exploratory and Confirmatory Factor Analyses (EFA and CFA), and convergent validity was tested using the Couple Satisfaction Index (CSI). EFA revealed a three-factor structure: discipline, childcare, and family processes, with strong internal consistency (α = 0.850–0.908). The CFA showed a good model fit, and PPC scores were negatively correlated with CSI. These findings indicate that the Indonesian PPC is a valid and reliable tool for assessing interparental conflict among new parents. It offers practical applications in research, counseling, and early intervention. Keywords: new parents, interparental conflict, parent problem checklist